Analisis Framming Pemberitaan Pilkada DKI Jakarta Tahun 2017 di Surat Kabar Harian Media Indonesia (Universitas Negeri Semarang, 2022)
Surya Paloh as the owner of the daily newspaper Media Indonesia, who is also the chairman of the National Democratic Party (Nasdem) has a major influence on news production in Media Indonesia. Regarding the support of the Nasdem party for the Basuki-Djarot pair in the 2017 DKI Jakarta Pilkada, of course, it has implications for the direction of Media Indonesia reporting which seeks to elevate the pair's political image amidst the issue of SARA that blew during the 2017 DKI Pilkada campaign. This is certainly not followed by the vision that Media Indonesia has, namely